Impact of the COVID-19 pandemic on corporate employer branding - Nelke, Astrid (Technium Social Sciences Journal, 2021)
The COVID-19 pandemic is disrupting the world of work. While before the pandemic most employees worked in an office, many employees are now experiencing hybrid workplaces and accelerated digitalisation on the job. These changes demand new leadership concepts and individual support for every single employee. Likewise, the employer branding of companies must undergo changes and be tailored to the novel situation. However, many companies must first readjust to the current circumstances. This involves a determined digitalisation of employer branding procedures and the adaptation of the employer brand communication both to the needs of the target groups and the requirements of the digital processes.